Characteristics of the innovation activities of firms in Europe: a critical review of international differences - Marek Vokoun (Review of Economic Perspectives, 2017)
A sample of 18 papers and 32 data sets revealed 210,404 firm level observations about European firms making decisions about innovation. A total of 66,965 observations describe activities of innovators between 1986 and 2008. This paper used a basic literature review to assess properties of innovation among quite rare full CDM (Crépon, Duguet, and Mairesse) papers. This study compared results from two systems of estimation and showed that both international and regional comparisons are rather problematic because of different definitions of innovation variables and data set representativeness. On average, a typical firm that engaged in innovation was a large firm competing in international markets in the sample of firms with 20+ employees. Smaller firms, however, invested more in research and development (R&D) and no linear relationship was found for output characteristics. Cooperation on R&D projects increased overall innovation intensity. There is strong evidence that public funding had an ambiguous effect on R&D spending and no additional effect on innovation output on average. This output measured by sales from innovated goods and services was on average in a positive relationship with labour productivity; however, a detailed view suggested this effect was present only in product innovation. In this paper, it is shown that results of innovation studies cannot be compared or used in research without deeper analysis of the data sample (micro companies, industries, active firms, entrants etc.), dependent variable (innovator, R&D expenditures, sales, productivity, new product, new service etc.) and the baseline company that is defined by independent variables.
Keywords: O33; L60; D24; O38; 330; Innovation; Europe; attributes; properties; decision to innovate; expenditures; value added